Pengembangan Arsitektur Otomatisasi Smart Home dengan Internet of Things - Arman Nuradi (Jurnal Sistem Cerdas, 2018)
Design of smart homes that meet the modern requirements that meet most of the consumer's living standards. Home security activities are supported by a real-time audio visual system that allows only entry of official visitors to the flats inserted in the system. Easy handling of selected home appliances in flats by enabling ON or OFF of each room is provided in the system. In addition, the remote control of the selected equipment is made through phone calls or by Internet that is accommodated in the system. The Home Assisted Home system software installed on the PC brings daily activities to the monitor screen as obtained from activities programmed in the database table. The electrical energy requirements of the home are partially supported by the extraction units of solar energy and wind energy. The electrical energy savings by these units are maximized by automatically changing the angle of solar panels and wind mills mounted on the terrace. Furthermore, the intruder detection unit entered in the system automatically calls the sequence of pre-programmed digits to deliver the message to a remote location while triggering the local alarm.